“Guyub Trisno” Fine Art Exhibition: Donation and Recovery of The COVID-19 Pandemic - Raharjo, Timbul; Triatmodjo, Suastiwi; Dafri, Yulriawan (Green Publisher Indonesia, 2023)
A pandemic is like a mirror that shows us the realities of life (Teng & Margaret, 2020). This fact of life is the importance of doing for humanity as did the artists of Trisno Guyub’s members. They initiated a joint exhibition for donations and recovery from the Covid-19 pandemic. This exhibition was attended by 118 artists and exhibited around 200 works of art, paintings and sculptures. The first purpose is an effort to share and the second is so that artists can fulfill their artistic expression. This study uses a qualitative method in the form of an explanation of the pandemic condition and how a group of Guyub Tresno conducts exhibition efforts as one of the recovery efforts. The pandemic period in various fields experienced significant social and economic changes in society. Life is relatively difficult and efforts to maintain and develop the arts continue. Artists generally focus on how to create works according to their intuition. Meanwhile the strategy of how the work can be distributed with a certain dowry during the pandemic is also relatively difficult. This also applies to other disadvantaged groups of people, namely orphans of course. Those experiencing the same problem may be more concerned. The limitations of children who have lost their parents as the foundation of life and learning to live are gone. Meanwhile, this happens to artists who are in a state of suspended animation. This exhibition is one of the positive forums for an honorable life and ways to share with others. The aim of this exhibition is recovery (Farah & Nasution, 2020) together with the way artists share with fellow artists and orphans. It is hoped that it can contribute to awakening the creative process of artists and can ease the burden on orphans affected by the Covid-19 Pandemic.